Biomaterials Inhomogeneities Detection by Electromagnetic Methods - Strapacova, Tatiana; Capova, Klara; Smetana, Milan (Communications - Scientific letters of the University of Zilina, 2011)
The paper deals with the biomaterials nondestructive testing using electromagnetic methods. The eddy current testing and electromagnetic - acoustic transducer methods are analyzed and applied for evaluation of conductive prosthetic materials. The defects detection results achieved by simulations and measurements using both methods are compared and discussed.